DESIGNING PUBLIC SERVICE ADVERTISING VIDEOS SELF HARASSMENT WITH MOTION GRAPHIC TECHNIQUES INFOGRAPHIC-BASED AS AN EFFORT TO INCREASE PUBLIC AWARENESS - Rama Dwissa Wiana; Dwika Lutfhi Permana (Yayasan Education and Social Center, 2021)
The development of the use of communication and computer technology requires people to be able to filter information and disseminate information that is useful for their social environment. As has happened recently, cases of verbal self-harassment through social media are quite widely discussed in Indonesia. Self harassment discussed is sexual harassment and body shaming. The purpose of this study is to produce a self-harassment public service advertising design with infographic-based motion graphic techniques as an effort to increase public awareness. This study uses a qualitative approach method, with interviews and also direct observation as well as literature studies and also existing studies. From the results of data collection, a concept was obtained, according to what was studied, namely